Empirical Monetary Macroeconomics: What Have We Learned in the Last 25 Years? - Brainard, William C.; Cooper, Richard N. (American Economic Review, 1975)
Monetary economics conveys the impression of great disagreement within the economics profession, and indeed the professional debates have often been heated. But behind the debates over policy there is a great deal of consensus on the importance of monetary variables for the working of national economies and on the mechanisms through which they exert their influence. title of this session reminds us that twenty-five years ago this was not so. When Howard Ellis wrote The Rediscovery of Money, the postwar revival had just begun. There was general skepticism about the ability of monetary policy to influence the economy, and the Oxford surveys were widely cited as the empirical basis for disbelief in the effect of monetary policy on investment. Despite the emergence in the intervening years of wide agreement about the importance of monetary policy, the empirical basis for many of our beliefs, and a fortiori for distinguishing among our differences, has remained weak. In casually accepting our present assignment, failed to appreciate just how complex the question posed in the title is. This is true even when the subject is confined, as here, to the monetary economics of the business cycle, leaving aside both microeconomic and steady-state growth considerations. What does it mean to say have learned something? And to whom does the we refer?